Formulation Design and In-vitro Ex-vivo Evaluation of Sustained Release Matrix Tablet of Tizanidine Hydrochloride by Direct Compression Method - Wajid, Syed (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: This study was undertaken to formulate and evaluate the sustained release (SR) matrix tablet of tizanidine hydrochloride by direct compression technique. Materials and Methods: SR matrix tablets of tizanidine were formulated using polymers such as carrageenan, xanthan gum, and polyethylene oxide (PEO) as releases retardants. All the pre-compressional parameters were found to be within the standard limits. Tablets were evaluated for hardness, friability, thickness, drug content, in-vitro release, and stability studies. In-vitro drug dissolution was studied. For 12 h using USP dissolution apparatus paddle type at the speed of 50 rpm at a temperature of 37 Â± 0.5Â°C using simulated gastric fluid (pH 1.2) and pH 6.8 phosphate buffer. Results: Matrix tablet with carrageenan, xanthan gum, and PEO successfully SR of tizanidine for a period of 12-h. The concentration of tizanidine was kept constant, microcrystalline cellulose-101, and lactose (1:3 ratio) used as filler. The maximum in-vitro release was found to be 97.8, 100.04, and 98.6 over a period of 12-h for formulations C4, X4, and P4. The data of in-vitro release from tablets were fitted to different kinetic models to explain the release profile. Conclusions: Formulations C4 and P4 were best fitted to Higuchi Fickian diffusion, whereas X4 formulation showed anomalous non-Fickian diffusion, i.e., the rate of solvent penetration and drug release are in the same range. Stability studies indicated that there was no change in the chemical and physical characteristics during the test period.